Pengembangan Sumber Daya Manusia terhadap Kinerja Dosen Dimediasi Motivasi pada Universitas Muara Bungo - Febri Silviana; Yudhi Novriansyah (Pusat Riset dan Inovasi Nasional, 2023)
The research purpose is to determine the influence of human resource development on lecturer performance mediated by motivational variables at Muara Bungo University. This research method is descriptive and uses quantitative analysis SmartPLS 3 analysis statistical test tool. The population is lecturers at Muara Bungo University. Using the Accidental Sampling technique were 33 Permanent Lecturers who served at the Faculty on social, economics and law. The results directly show that Human Resources Development is not significant (P-Values ​​0.232 > 0.05) and has no effect on lecturer performance (t-statistics 1.196 < t-table 1.96). Human Resources Development is significant (P-Values ​​0.000<0.05) and has an effect on motivation (t-statistic 109.356>1.96). Motivation is significant (p-Values ​​0.000<0.05) and influences Lecturer Performance (t-statistics 5.729 > t-table 1.96). Furthermore, indirectly, it shows that Human Resources Development is significant (P-Values ​​0.001 <0.05) and has an effect on Lecturer Performance Mediated by Motivation (t-statistic 5.662 > 1.96). It is recommended that the Rector of Muara Bungo University choose the type and method of human resource development and continue to motivate subordinates to have an impact on improving lecturer performance.